Kontestasi dan Survivalisme Media Dakwah di Tengah Liberalisasi Industri Media: Analisis Media TV-9 Jawa Timur - Surokim, Surokim (Jurnal Komunikasi Islam, 2019)
Local television has faced sharp contestation and interplay between actors and agents. As a proselytising TV, TV-9 has faced a dilemma between social functions and corporate functions. In this regard, as a da'wah media, it tends to uphold the religious social mission, while as a corporate media it is required to make a profit. This article is a critical study of how the contestation took place and how the survival of TV-9. The results of this study indicate that TV-9 has developed the concept of entertained da'wah in overcoming the contestation, namely da'wah as substance, while entertainment as the complement of the TV program. Additionally, TV-9 also tried to resonate the da'wah strategy with the cultural paths of the past and present that have existed within society.